Moving Education and Individual Education as of Communities Health Education Models in Health Emergency Conditions (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Health education in the community is a part that must receive special attention during health emergencies. The research objective was to obtain the results of the implementation of the Moving Education and Individual Education models as the basis for the model of health education in the community during health emergencies. Research using experimental research (pre-test and post-test group). It took place in Semarang City in 2022. The population is 3616 people. The sample is determined by an accidental sampling technique that meets the requirements (age over 40 years, willingness to be a respondent, participating in Moving Education or Individual education activities). The statistical test results for the difference in the behavior of respondents before and after the intervention with the Moving Education and Individual Education Models obtained a p-value = 0.002 (p 0.05), or there was a difference between the two extension methods. The Individual Education method is stated to be more effective than the Moving Education method in implementing health protocols, but the impact on other factors is an important consideration.